IMPLEMENTASI STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK PEROLEHAN BELAJAR KONSEP NORMA DI SMP - Mustaan, Mustaan; Aunurrahman, Aunurrahman; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to (1) find the Pancasila and Civic Education learning plan using problem solving strategy, (2) to describe the implementation of Pancasila and Civic Education learning using problem solving strategy, (3) to describe learning evaluation with problem solving strategy, and (4) to describe the learning achievement of students in achieving the acquisition of learning the concept of norms in the learning of Pancasila and Civic Education by using problem solving strategy in class SMP This research is a qualitative descriptive research to study "Application of problem solving strategy with in-depth interview data collection technique, participant observation, document study, and triangulation. Data analysis techniques ranging from data dispersion, data reduction, data reflection, and conclusion. The results showed that the design of Pancasila and Civic Education learning using problem-solving strategy for learning acquisition of the concept of norms was prepared in accordance with the components of the implementation plan of learning (RPP) that is to determine the competence standards, basic competencies, indicator. Keywords: implementation, problem-solving strategies, learning concept acquisition